2017
DOI: 10.1140/epjp/i2017-11708-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanosize effect of clay mineral nanoparticles on the drug diffusion processes in polyurethane nanocomposite hydrogels

Abstract: Abstract. Studies of swelling and release of naproxen sodium (NAP) solution by polyurethane nanocomposite hydrogels containing Cloisite 30B (organically modified montmorillonite (OMMT)) have been performed. Polyurethane nanocomposite hydrogels are hybrid, nontoxic biomaterials with unique swelling and release properties in comparison with unmodified hydrogels. These features enable to use nanocomposite hydrogels as a modern wound dressing. The presence of nanoparticles significantly improves the swelling. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…In our previous paper [16], we demonstrated the nanosize effect of the nanofiller on the kinetics of the swelling and release of naproxen sodium from polyurethane nanocomposite hydrogels with two different weights of poly(ethylene oxide) doped with various amount of Cloisite® 30B. It was shown that the presence of nanoparticles improves the swelling and also hinders drug diffusion from polymer matrix and consequently slows down the drug release.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…In our previous paper [16], we demonstrated the nanosize effect of the nanofiller on the kinetics of the swelling and release of naproxen sodium from polyurethane nanocomposite hydrogels with two different weights of poly(ethylene oxide) doped with various amount of Cloisite® 30B. It was shown that the presence of nanoparticles improves the swelling and also hinders drug diffusion from polymer matrix and consequently slows down the drug release.…”
Section: Introductionmentioning
confidence: 96%
“…In our previous paper [16], we investigated the swelling and release of naproxen sodium from polyurethane nanocomposite hydrogels with two different molecular weight of PEG, doped with various amounts of nanofiller-organically modified montmorillonite with quaternary ammonium salt (Cloisite® 30B). In particular, we examined the influence of this nanofiller on the kinetics of both processes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations